Current trends in high-level synthesis of asynchronous circuits - Sparso, J. (2009 16th IEEE International Conference on Electronics, Circuits and Systems - (ICECS 2009), 2009)
This paper is a survey paper presenting what the author sees as two major and promising trends in the current research in CAD-tools and design-methods for asynchronous circuits. One branch of research builds on top of existing asynchronous CAD-tools that perform syntax directed translation, e.g. the Haste/TiDE tool from Handshake Solutions or the Balsa tool from the University of Manchester. The aims are to add high-level synthesis capabilities to these tools and to extend the tools such that a wider range of (higher speed) micro-architectures can be generated. Another branch of research takes a conventional synchronous circuit as the starting point, and then adds some form of handshake-based flow-control. One approach keeps the global clock and implements discrete-time asynchronous operation. Another approach substitutes the clocked registers by asynchronous handshake-registers, thus creating truly continuous-time asynchronous circuits that operate without a clock. The perspective here is that the substitution/conversion is done as the final step in an otherwise conventional synchronous design flow.